Association between serum osteoprotegerin level and mortality in kidney transplant recipients ‐ a prospective observational cohort study. (18th March 2021) - Gupta, Vardaan; Ekundayo, Oladapo; Nemeth, Zsofia K.; Yang, Yifan; Covic, Adrian; Mathe, Zoltan; Kovesdy, Csaba P.; Molnar, Miklos Z.; Mucsi, Istvan
Abstract: Paradoxically, higher serum levels of osteoprotegerin (OPG: a vascular calcification inhibitor) have been associated with increased arterial stiffness, risk of cardiovascular disease and all‐cause mortality. A few studies reported that post‐transplant OPG levels are associated with mortality in kidney transplant (KT) recipients. In this study, this association was assessed in a cohort of prevalent KT recipients, adjusting for previously untested potential confounders, including fibroblast growth factor 23 (FGF23) and interleukin 6 (IL‐6). Socio‐demographic and clinical parameters, medical and transplant history, and laboratory data were collected from 982 prevalent KT recipients. The association between serum OPG and all‐cause mortality over a 6‐year follow‐up period was examined using Kaplan–Meier survival curves and multivariable‐adjusted Cox regression models. Participants with high serum OPG were more likely female, older, deceased donor KT recipients and have more comorbidity, lower eGFR, higher FGF23, higher IL‐6, and longer dialysis vintage. Each 1 pmol/l higher serum OPG level was associated with a 49% higher risk of mortality (hazard ratio (HR) [95% confidence interval (CI)]: 1.49 [1.40–1.61]). This association persisted after adjusting for confounders (HR [95% CI]: 1.20 [1.10–1.30]). In conclusion, serum OPG was associated with all‐cause mortality independent of several novel confounders in prevalent KT recipients.